y-y1=m(x-x1)
that is the equation of a line that passes through the point (x1,y1) and has a slope of m
slope between (x1,y1) and (x2,y2) is (y2-y1)/(x2-x1)
so first convert them to common denomenator which is 10
[tex]( \frac{8}{10} , \frac{2}{10} )[/tex] and [tex]( \frac{5}{10} , \frac{15}{10} )[/tex]
slope=[tex] \frac{\frac{15}{10}-\frac{2}{10}}{ \frac{5}{10}-\frac{8}{10} } = \frac{\frac{13}{10}}{ \frac{-3}{10} } = \frac{13}{-3}= \frac{-13}{3} [/tex]
a point is [tex]( \frac{1}{2} , \frac{3}{2} )[/tex]
so
[tex]y-\frac{3}{2}=\frac{-13}{3}(x-\frac{1}{2})[/tex]
[tex]y-\frac{3}{2}=\frac{-13}{3}x+\frac{13}{6}[/tex]
times both sides by 6
[tex]6y-9=-26x+13[/tex]
[tex]6y=-26x+22[/tex]
[tex]y= \frac{-13}{3}x+ \frac{11}{3} [/tex] or in standard form